Influence of DMDBS on the morphology and mechanical properties of polypropylene cast films - Sreenivas, K.; Pol, Harshawardhan V.; Kumaraswamy, Guruswamy (Polymer Engineering and Science, 2011)
We investigate extrusion film casting (EFC) of polypropylene (PP) and examine the effects of varying the concentration of nucleating agent, dimethyl dibenzylidene sorbitol (DMDBS); melt temperature at the die exit; and the draw ratio. Addition of DMDBS increases the PP crystallization temperature, and consequently the PP lamellar repeat spacing. For the draw ratios explored, we do not observe any substantial orientation of iPP crystals for films of neat iPP. However, addition of DMDBS results in the formation of oriented PP crystals, with greater orientation for higher draw ratios. On cooling from the melt, a network of DMDBS nanofibers forms in the PP. We believe that flow-alignment of this DMDBS network templates the orientation of PP crystals. We observe that the tensile modulus and yield stress increase with PP crystal orientation. However, at high DMDBS concentrations (0.8%), films have poor mechanical strength due to formation of voids and defects. POLYM. ENG. SCI., 51:2013-2023, 2011. (C) 2011 Society of Plastics Engineers

Phase separation of DMDBS from PP: effect of polymer molecular weight and tacticity - Sreenivas, K.; Basargekar, Rajeev; Kumaraswamy, Guruswamy (Macromolecules, 2011)
We report an unexpected dependence of DMDBS phase separation temperature on the molecular weight of the matrix isotactic polypropylene (iPP). DMDBS crystallizes out at lower temperatures for iPP with decreasing molecular weight (and correspondingly lower tacticity). All the iPPs in our study are reasonably high molecular weight samples and there is no molecular weight dependence of their solubility parameter. Therefore, the decrease in DMDBS phase separation temperature for lower molecular weights cannot be rationalized using thermodynamic arguments. This molecular weight dependence appears to be unique to isotactic polypropylene and is not observed for either syndiotactic polypropylene or for random copolymers of isotactic polypropylene containing ethylene comonomer.

Fine-tuning the balance between crystallization and gelation and enhancement of CO2 uptake on functionalized calcium based MOFs and metallogels - Mallick, Arijit; Schoen, Eva-Maria; Panda, Tamas; Sreenivas, K.; Diaz, David Diaz; Banerjee, Rahul (Journal of Materials Chemistry, 2012)
The synthesis, structure, gas adsorption and catalytic properties of a new 3D porous, crystalline metal-organic framework (Ca-5TIA-MOF) as well as stable viscoelastic metallogels (Ca-5TIA-Gel) are reported. Remarkably, the preparation of both types of materials can be carried out starting from the same organic ligand (i.e. 5-(1,2,4-triazoleyl) isophthalic acid (5TIA)), divalent metal ion (i.e. Ca(II)) and organic solvent (i.e. DMF). In this particular case, the presence of water in the solvent system favors the formation of a crystalline MOF, whereas a pure organic solvent induces gelation. The characterization of the materials was carried out using a series of techniques including XRD, FT-IR, TGA, TEM, SEM, SAXS and dynamic rheology. Experimental PXRD peaks of both Ca-5TIA-xerogel and Ca-5TIA-MOF matched reasonably well with simulated PXRD, suggesting the presence of, at least, some common structural elements in the 3D networks of both xerogel and crystalline phases. Moreover, the nature of the metal counteranion was found to have a critical influence on the gelation phenomenon. To the best of our knowledge, this report describes unprecedented Ca-based LMW-metallogels, as well as the first porous Ca-based MOF, which shows adsorption capacity for CO2 at 1 atm pressure. Interestingly, Ca-5TIA-xerogel presented 20% higher CO2-uptake than the crystalline Ca-5TIA-MOF at 1 atm and 298 K. Both Ca-5TIA-MOF and Ca-5TIA-Gel also displayed a modest catalytic activity towards the hydrosilylation of benzaldehyde, with slightly better performance for the gel phase material.

Large amplitude oscillatory shear induces crystal chain orientation in velocity gradient direction - Sreenivas, K.; Kumaraswamy, Guruswamy (ACS Macro Letters, 2014)
Imposition of large amplitude oscillatory shear (LAOS) on crystallizing polymer melts results in lamellar orientation in the shear gradient direction, in contrast to the flow-orientation observed for steady shear. LAOS enhances the formation of plate-like nuclei and orients their normals in the gradient direction. An Arrhenius temperature dependence (with activation energy approximate to 226 kJ/mol) characterizes the relaxation of crystal orientation with annealing.